2021
DOI: 10.1063/5.0056824
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic spectral features via trajectory-based quantum dynamics: A perturbative analysis of the interplay between dynamics and sampling

Abstract: The performance of different approximate algorithms for computing anharmonic features in vibrational spectra is analysed and compared on model and more realistic systems that present relevant nuclear quantum effects. The methods considered combine approximate sampling of the quantum thermal distribution with classical time propagation and include Matsubara dynamics, path integral dynamics approaches, linearized initial value representation and the recently introduced adaptive quantum thermal bath. A perturbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…45 Because two-dimensional Raman and hybrid THz-Raman spectra vanish for harmonic potentials with linear dipole moment or polarizability operators, 56 adequate computational approaches must capture the effect of electrical and mechanical anharmonicities, which poses a challenge for RPMD and the above-mentioned methods. 59,64 To derive the equilibrium-nonequilibrium RPMD, we did not invoke the concept of the Kubo transformation, which is done traditionally for one-time correlation functions, 35…”
Section: Discussionmentioning
confidence: 99%
“…45 Because two-dimensional Raman and hybrid THz-Raman spectra vanish for harmonic potentials with linear dipole moment or polarizability operators, 56 adequate computational approaches must capture the effect of electrical and mechanical anharmonicities, which poses a challenge for RPMD and the above-mentioned methods. 59,64 To derive the equilibrium-nonequilibrium RPMD, we did not invoke the concept of the Kubo transformation, which is done traditionally for one-time correlation functions, 35…”
Section: Discussionmentioning
confidence: 99%
“…It can be shown that the overtone intensity is underestimated by approximately a factor of two due to the absence of position-momentum correlation in the QTB phase space sampling [43,44]. This error on the overtone intensity can be detected (and potentially corrected) using the first-kind fluctuation-dissipation theorem criterion defined in Section 7, and it remains limited compared to that of path integral methods (see Section 6), which yield a much lower overtone intensity, similar to that of classical simulations [16].…”
Section: A 'Mildly' Anharmonic Examplementioning
confidence: 99%
“…Similar shifts are observed between the classical, QTB and exact quantum results as for the main resonance. The detailed perturbation analysis performed in [16] shows that an analogy can be drawn between the QTB and linearized semiclassical initial value representation (LSC-IVR) methods, that combine quantum phase space sampling with classical molecular dynamics for the evaluation of time correlation functions [41,42]. Indeed, in QTB simulations, the short-term dynamics is essentially classical, whereas the coupling with the bath introduces quantum statistics in the phase space sampling.…”
Section: A 'Mildly' Anharmonic Examplementioning
confidence: 99%
See 2 more Smart Citations